Invited commentary: The politics of human embryo research and the motivation to achieve PGD - Yovich, John (2011)
The idea that biomedical research can be influenced by political events implies a teleological basis indicating that scientific achievements occur because there is a political need. Such a concept appears to have been the reason PGD was fast-tracked to emerge as a biomedical achievement well before its due date, occurring at a time when human embryology was still struggling to reach a reasonable level of efficiency and become adopted as a clinically relevant advance around the world. One story underlying the historical achievement of the HFE Act 1990, enabling regulated embryo research, steps outside the firm ground of biomedical science and encourages the idea that Reproductive BioMedicine Online should embrace a further section enabling articles dealing with 'History, politics and personalities' where these influence biomedical research. © 2011, Reproductive Healthcare Ltd. All rights reserved.